Neural and behavioral evidence of free shipping on consumer decision making - Youngju Lee; Yoonsang Lee; Kyeong Seob Song; Ji-Won Chun; Dongha Lee (PLoS ONE, 2026)
The rise in online shopping has heightened consumer frustration, as many are reluctant to pay additional charges. Understanding the neural mechanisms of decision-making underlying this resistance could provide key insights into consumer behavior. However, research on these neural correlates remains limited. To address this gap, we conducted a functional magnetic resonance imaging (fMRI) study examining the relationship between shipping fee combinations and purchasing decisions. During fMRI scanning, 40 participants evaluated their intention to purchase shoes with varying shipping fees, while the total price remained constant. Behavioral measures included purchase intention rating, reaction time (RT), and the Rate Intention Score, calculated by dividing the mean purchase intention score by RT. Behavioral data revealed a clear preference for free shipping, with distinct blood-oxygenation-level-dependent (BOLD) responses in free shipping choices across shipping fee conditions. Comparisons between free shipping and the lowest shipping fee showed strong emotional preferences for free shipping, reflected in positive BOLD signals of the medial prefrontal cortex (PFC). fMRI analysis revealed that the most significant differences stemmed from variations in shipping fees, particularly between free shipping and the lowest shipping fee, highlighting the unique appeal of free shipping. As shipping fees increased, emotional influences diminished, shifting cognitive processing to the ventrolateral PFC. Additionally, increased BOLD responses in the precentral gyrus under the free-shipping option indicated its involvement in decision execution. An integrated behavioral and neural data analysis offers valuable insights into the mechanisms that influence real-world purchasing decisions.